(untitled) (Ozone Therapy Global Journal, 2018)
Diabetic foot ulcers in Diabetes type 2 patients are consider a medical emergency and a public health problem, being the mean cause of hospital incomes and amputation. Is consider a multifactorial disease in which are involved venous insufficiency, motor and sensitive peripheric neuropathy, immunosuppression, oxidative stress, post-translational modifications developing claudication, dumbness in feet, anhidrosis, hyperkeratosis, helomas, dryness, no perceptible cutaneous loss integrity leading to ulcers, infections and gangrene. A multidisciplinary approach is recommended to deal with metabolic disorder, mobility, ulcer healing. Our proposal is to include ozone therapy as medical treatment for diabetic foot ulcers and diabetes. In the four cases that we presented with chronic infected diabetic foot ulcers diagnosis, we proposed an eight weeks multidisciplinary treatment included, diet, hygienic and general indications, pharmacological treatment for diabetes and venous insufficiency, physiotherapy and parenteral (ozonized saline solution), and local ozone therapy (ozonized olive oil and hermetic boot) in which we observed at the end of the treatment a glycemic low down at normal levels, a total ulcer healing and a recover of the claudication symptoms. .